Intense pulsed light for inactivating planktonic and biofilm molds in food - Li, Xuejie; Gu, Nixuan; Ye, Yanrui; Lan, Haifeng; Peng, Fang; Peng, Gongyong (Frontiers in Microbiology, 2023)
It has been reported that about a quarter of the world’s agriculture products is unable to be consumed each year because of mold contamination, resulting in incalculable economic losses. Despite modern food technology and the various preservation techniques available, the problem of mold contamination of food is still not adequately controlled. In this study, we simulated the biofilm formed by Aspergillus niger and Penicillium glaucum in liquid and solid food in 96 well cell culture plates and polycarbonate membrane models, respectively, and investigated the fungicidal effect of IPL on planktonic and biofilm molds at three different capacitance parameters at room and refrigerator temperatures. The results show that IPL can achieve fungicidal rates of over 99% for planktonic molds and over 90% for biofilm molds, and that the smaller the capacitance, the more frequent the irradiation required to achieve the same fungicidal rate. In addition, temperature, A. niger or Penicillium glaucum have no effect on the fungicidal effect of IPL. We believe that IPL is a promising non-thermal physical sterilization technique for fungal inhibition on food surfaces.